Influence of osmotic dehydration on color and texture of pork meat - Knežević Violeta; Ćurčić Biljana; Filipović Vladimir; Nićetin Milica; Lević Ljubinko; Kuljanin Tatjana; Gubić Jasmina (Journal on Processing and Energy in Agriculture, 2013)
In this work instrumental analysis of color and texture of fresh and osmotically dehydrated samples of pork meat (in three different osmotic solutions solutions R1: NaCl+sucrose+water, R2: R1+ molasses, 1:1, R3: molasses) was carried out. Results obtained for fresh and dehydrated meat in three different solutions were compared. The results obtained in the analysis of instrumental colors, showed a statistically significant difference between the samples of raw meat and dehydrated samples. From the comparative results, there are statistically significant difference between the R1 dehydrated meat and meat dehydrated in R2 and R3. The values of texture parameters that were monitored showed that the same trends were statistically significant, i.e. process of osmotic dehydration led to increase of these values for the dehydrated meat samples in all investigated osmotic solutions. The results obtained by instrumental analysis are in accordance with the results obtained by descriptive sensory analysis.